Denosumab May Increase the Risk of Local Recurrence in Patients with Giant-Cell Tumor of Bone Treated with Curettage. (21st March 2018) - Errani, Costantino; Tsukamoto, Shinji; Leone, Giulio; Righi, Alberto; Akahane, Manabu; Tanaka, Yasuhito; Donati, Davide Maria
Abstract : Background: Recent clinical studies have suggested that denosumab is associated with tumor response and reduced surgical morbidity in patients with giant-cell tumor of bone (GCTB). We therefore evaluated the recurrence-free survival rate of patients who had GCTB in an extremity and were treated with surgery and denosumab, to determine the influence of denosumab and clinical factors on the risk of local recurrence. Methods: We retrospectively reviewed the medical records of 408 patients treated for GCTB in an extremity in a single institution from 1990 through 2013. Two hundred and forty-seven patients underwent curettage (intralesional surgery) with a high-speed burr, and 161 underwent resection. Phenol adjuvant was used in 221 of the 247 patients who had curettage. We also reviewed the medical records of 30 patients treated surgically (25 with curettage and 5 with resection) and with denosumab from 2010 through 2013 and compared their clinical results with 378 historical control subjects. The overall minimum duration of follow-up was 24 months. Results: The local recurrence rates were 60% (15) of 25 patients treated with curettage and denosumab and 16% (36) of 222 patients treated with curettage alone. The joint preservation rates were 80% (20) of 25 patients treated with curettage and denosumab and 94% (209) of 222 patients treated with curettage alone. Univariate and multivariable analyses showed that denosumab was the only independent factor associated with a poor prognosis when recurrence-free survival and joint preservation were considered. The overall median duration of follow-up was 85.6 months (interquartile range, 54.3 to 125.1 months). Viable tumor was present in all 30 specimens from patients treated with denosumab. Conclusions: There was a higher rate of recurrence in the cohort exposed to denosumab. Because there were substantial differences in the cohorts and randomization was not applied, however, causation could not be evaluated. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.